Developing a Suitable Methodology for Integrated Supply Chain Analysis in the Australian Beef Industries: a Research Proposal - Jie, Ferry; Parton, Kevin; Cox, Rod (Journal the Winners: Economics, Business, Management, and Information System Journal, 2005)
The Australian Beef Supply Chain is the chain or sequence of all activities from the breeding property to the domestic or overseas consumers. The objective of this research is to describe beef supply chains in Australia and to explore and measure the performance of such chains (i.e. efficiency, effectiveness, and productivity). In addition to this it is to suggest alternative configurations for these supply chains that enhance performance of the businesses concerned and to develop a new design methodology for integrated supply chains based on process modeling, performance analysis and optimization of production and inventory distribution networks.